Genetic mapping and QTL analysis for peanut smut resistance - de Blas, Francisco Javier (2021)
Fil: De Blas, Francisco Javier. Universidad Nacional de Córdoba. Instituto Multidisciplinario de Biología Vegetal (IMBIV); Argentina.